Stroke rehabilitation - Harsono, Harsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
Patients with stroke, particularly during the hours following the acute episode, are in evolution, undergo various stages of pathophysiological readjustment. The brain lesion plays an important role in this process. In addition to affecting the central nervous system function, it keeps a close pathophysiological relationship with the respiratory system, the circulatory system, and all systems that participate in keeping the internal milieu in balance. These systems are often altered secondary to the brain lesion, but in other cases they are directly or indirectly responsible for the brain lesion or are worsening.The pathophysiological interrelation in all seriously ill or potentially seriously ill patients is of great importance, and of course, the same is true in stroke patient. Hence management is required that the treatment should be integrated and not divided by systems or according to the various medical specialties. The importance of comprehensive rehabilitation for the stroke patients with complex physical, psychic and social problems should be underlined. Medical, social, psychological and vocational measures must start early. They must be coordinated and usually applied more or less simultaneously.Key Words: stroke- internal milieu-medical specialty-management of treatment- comprehensive rehabilitation